2021
DOI: 10.47750/cibg.2021.27.02.195
|View full text |Cite
|
Sign up to set email alerts
|

Heads of Departments Leadership Styles, Work Climate and Organizational Commitment Enhance the Job Performance of University Lecturers

Abstract: For survival in the environment and increase organizational success it is mandatory for any organization to focus on enhancing employees' job performance. The main objective of this study was to determine the correlation of leadership styles, work climate and organizational commitment with job performance. The public universities lecturers were selected as population of the study while 339 lecturers were administered as a sample for this study through stratified random sampling technique. Data was collected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, leadership behavior has a positive and significant effect on the performance of educational staff, thus confirming the theory presented byLuthans (2006) inRapiuddin et al, (2021);and Salman et al, (2023) that leadership leads to high performance in organizations. This has also been proven by previous researchers such asAlzghoul et al, (2023);Qalati et al, (2022);Zamin & Hussin, (2021);Rapiuddin et al, (2021);Titisari et al, (2020);Colquitt et al, (2018); and(Saleem & Amin, 2013). The implementation of leadership behavior in improving performance at the Kendari State Islamic Institute is capable of bringing about a change (performance improvement) in the leadership role.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, leadership behavior has a positive and significant effect on the performance of educational staff, thus confirming the theory presented byLuthans (2006) inRapiuddin et al, (2021);and Salman et al, (2023) that leadership leads to high performance in organizations. This has also been proven by previous researchers such asAlzghoul et al, (2023);Qalati et al, (2022);Zamin & Hussin, (2021);Rapiuddin et al, (2021);Titisari et al, (2020);Colquitt et al, (2018); and(Saleem & Amin, 2013). The implementation of leadership behavior in improving performance at the Kendari State Islamic Institute is capable of bringing about a change (performance improvement) in the leadership role.…”
supporting
confidence: 77%
“…in their research concluded that leadership behavior is able to positively and significantly influence the performance produced by employees. Furthermore,Titisari et al, (2020) also explained that good leadership behavior applied in an organization will have an impact on the good performance provided by employees Zamin & Hussin, (2021)(Rapiuddin et al, 2021) also concluded that leadership can have a positive and significant influence on performance.…”
mentioning
confidence: 99%
“…The study on leadership styles, work climate and organisational commitment enhancing the job performance of university lecturers, on a sample size of 339 lecturers in public universities in Malaysia using statistical package for social sciences (SPSS -25) to analyse the hypotheses concluded that the three constructs could predict job performance of lecturers [33].…”
Section: Studies On Organisational Commitment and Job Productivitymentioning
confidence: 99%
“…showed the mean and standard deviation scores of participatory managements, performance appraisal system, organisational commitment and lecturers' job productivity of lecturers in Lagos and Ogun state owned universities. The mean performance appraisal score in state universities was 144.06 with standard deviation score of33.478. Participatory management is 53.98 mean score (std.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that strong leadership skills in school management ensure efficient utilization of educational resources. Though studies suggest that education administration, particularly head management skills, play a vital role in school management (Klausmeier, 1985; Reynolds & McKimm, 2021;Munie et al, 2020; Malik & Akram, 2020; Muriuki et al, 2020), most studies on head management skills focus upon their impact on the competencies or leadership roles used for realizing the different tasks and outcomes (Zamin & Hussin, 2021; Edinyang et al, 2020;Yılmaz & Aslan, 2013).…”
Section: Introductionmentioning
confidence: 99%